Gas‐Sensing Activity of Amorphous Copper Oxide Porous Nanosheets. Issue 1 (17th January 2020) - Tian, Zheng; Bai, Hua; Li, Yahui; Liu, Wei; Li, Junfang; Kong, Qinghong; Xi, Guangcheng
Abstract: In this paper, the gas‐sensing properties of copper oxide porous nanosheets in amorphous and highly crystalline states were comparatively investigated on the premise of almost the same specific surface area, morphology and size. Unexpectedly, the results show that amorphous copper oxide porous nanosheets have much better gas sensing properties than highly crystalline copper oxide to a serious of volatile organic compounds, and the lowest detection limit (LOD) of the amorphous copper oxide porous nanosheets to methanal is even up to 10 ppb. By contrast, the LOD of the highly crystalline copper oxide porous nanosheets to methanal is 95 ppb. Experiments prove that the oxygen vacancies contained in the amorphous copper oxide porous nanosheets play a key role in improving gas sensitivity, which greatly improve the chemical activity of the materials, especially for the adsorption of molecules containing oxygen‐groups such as methanal and oxygen. Abstract : The gas‐sensing properties of copper oxide porous nanosheets in amorphous and highly crystalline states were comparatively investigated on the premise of almost the same morphology, specific surface area, and pores. Experiments and theoretical simulations together prove that amorphous copper oxide porous nanosheets have much better gas sensing properties than highly crystalline copper oxide to a serious of volatile organic compounds.